RELATIONSHIPS BETWEEN EMPLOYMENT AND GROWTH FROM INDUSTRIAL PERSPECTIVE BY CONSIDERING EMPLOYMENT INCENTIVES: THE CASE OF TURKEY - Emre Aksoy (International Journal of Economics and Financial Issues, 2013)
By using quarterly data this study applied Toda-Yamamoto (1995) method for the period 1988-2010 to uncover the relationship between growth and employment in aggregate and industrial respects and also to investigate the impacts of investment and employment incentives on employment for Turkish Economy. The findings showed that the relationship between growth and employment varied with the industries. The study covers ten industries and there were causalities detected for four out of ten industries, either one or two ways. For the rest six industries covered in the study, there was no causal relationship obtained. The incentives impacts on employment, similarly, vary with industries. The law numbered as 5084 had positive and statistically significant influences on social service, manufacturing, and transportation and communication industries while the law numbered as 5763 extracted positive and significant influences on energy production and distribution, and financial intermediation industries.